Penggunaan Idol K-Pop New Jeans sebagai Brand Ambassador Indomie - A' izza, Hanna; Salisah, Nikmah Hadiati (Jurnal Audiens, 2025)
This research aims to analyze Indomie's marketing strategy in introducing its newest product through collaboration with K-Pop group NewJeans as a brand ambassador. The A-T-R (Awareness-Trial-Reinforcement) theory is used to describe the stages of awareness, trial, and reinforcement in building consumer loyalty. This research uses a qualitative approach with descriptive analysis, focusing on the utilization of pop culture through campaigns on social media such as Instagram and TikTok. Primary data was collected through participatory observation of the campaign, as well as secondary data from relevant literature. Data collection techniques involved documentation and literature study, which were analyzed using the content analysis method. The findings show that the collaboration with NewJeans was effective in raising brand awareness, encouraging consumers to try the product, and strengthening consumer loyalty. This research provides insights into the role of influencers in marketing strategies amidst the influence of pop culture, as well as its impact on local brands in the global market.